Adaptation and validation of the Juvenile Victimization Questionnaire-R2 for a national study of child maltreatment in Australia. (May 2023) - Mathews, Ben; Meinck, Franziska; Erskine, Holly E.; Tran, Nam; Lee, Ha; Kellard, Karen; Pacella, Rosana; Scott, James G.; Finkelhor, David; Higgins, Daryl J.; Thomas, Hannah J.; Haslam, Divna M.
Abstract: Background: To establish national prevalence of child maltreatment, reliable, valid and contextually appropriate measurement is needed. This paper outlines the refinement, adaptation and testing of child maltreatment sections of the Juvenile Victimization Questionnaire (JVQ)-R2 for use in the Australian context. Methods: Three phases were undertaken: 1) Conceptual analysis of the five forms of child maltreatment (physical abuse, sexual abuse, emotional or psychological abuse, neglect, and experience of domestic violence), item mapping and review, item development, and independent expert review; 2) Cognitive testing with members of the general population, and individuals who have experienced maltreatment; and 3) Pilot testing and quantitative psychometric assessment with a random sample of Australians aged 16–65+ years. Results: The final measure included a total of 17 child maltreatment screener items, assessing Physical Abuse (2 items), Sexual abuse (5 items (including 2 non-contact items and 3 contact items), Emotional Abuse (3 items), Neglect (3 items), and Experience of Domestic Violence (4 items). Screener items were also included on corporal punishment (1 item), and internet sexual victimization (2 items). The final 17-item revised JVQ had high face and conceptual validity and good internal reliability (α = 0.86 and Ω = 0.87). Test re-test reliability was moderate to high for individual screeners ranging from k = 0.45 to 0.89. Conclusions: Results indicate the Juvenile Victimization Questionnaire-R2: Adapted Version ( Australian Child Maltreatment Study ) is a suitable instrument for assessing population-wide prevalence of maltreatment. It is congruent with conceptual models of maltreatment and shows good reliability and validity in this Australian sample.